Judicial Analysis of Defendant Acquittal in Human Exploitation Cases: A Study on Evidentiary Principles in Criminal Law - Irvan; Panjaitan, Budi Sastra (Universitas Islam Negeri Alauddin Makassar, 2025)
This research analyzes the judicial considerations in Decision Number 555/Pid.Sus/2023/PN STB, which acquitted the former Regent of Langkat, TRPA, in a human exploitation case. The study evaluates whether the judges' reasoning aligns with the legal provisions of Law Number 21 of 2007 on the Eradication of Human Trafficking and Law Number 39 of 1999 on Human Rights. This study employs a normative juridical approach, focusing on court decisions, statutory regulations, and relevant legal theories in criminal law and human rights. The analysis is conducted through doctrinal research, examining the legal reasoning behind the verdict and its conformity with established legal principles. The findings indicate that the court ruled the indictment’s elements were not legally and convincingly proven. The judges based their decision on the principle of presumption of innocence, emphasizing the lack of sufficient evidence to establish the defendant’s direct involvement. The absence of mens rea (malicious intent), material benefits from exploitation, and direct participation in acts of violence further supported the acquittal. Additionally, accountability for the crime had already been attributed to another perpetrator in a prior ruling. This study contributes to the discourse on evidentiary standards and judicial reasoning in human exploitation cases. It offers a critical assessment of the challenges in prosecuting high-ranking officials and the legal gaps that may affect accountability in similar cases. The findings highlight the need for a more robust evidentiary framework in human exploitation trials, particularly in cases involving structural actors. The study suggests that legal reforms and enhanced prosecutorial strategies are necessary to prevent loopholes that could hinder justice in crimes of exploitation and human trafficking.